Pd/C Catalyzed Dehalogenation of (Hetero)aryls Using Triethylsilane as Hydrogen Donor - La Torre, Mathéo; Maton, William; Cleator, Ed; Jouffroy, Matthieu (Synthesis, 2023)
(Hetero)aryl dehalogenation is a classical transformation usually performed using hydrogen gas and a metal supported on carbon, notably palladium (Pd/C). Though efficient, the need for a milder and operationally simple dehalogenation can arise. We found that the combination of Pd/C as catalyst and triethylsilane (TES) as hydrogen donor in THF resulted in a broadly applicable, easy to set up, and scalable debromination and deiodination. Optimization of the reaction showed that 1 mol% of Pd/C and 4 equiv of TES at room temperature were sufficient to obtain full conversion of most synthons of pharmaceutical interest in 4–24 h. The newly found conditions were applied to a large range of aromatic and heteroaromatic substrates, affording the desired targets in good to excellent yields with an exceptional functional group tolerance.
Keywords: dehalogenation; triethylsilane; Pd/C; aryl; heteroaryl